MENINGKATKAN HASIL BELAJAR IPS MELALUI MEDIA GAMBAR PADA SISWA KELAS IV SD NEGERI 3 MOLONA - Kasih, Waode Mitra (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to “Improving Social Studies Learning Outcomes through Image Media in Class IV Students of SD Negeri 3 Molona ​​South Buton Regency”. This research conducred in 2 cycles, each cycle includes: planning, implementation, observation, and reflection. The subjects of this study were the fourth grade students of SD Negeri 3 Molona for the 2020/2021 academic year, totaling 20 students consisting of 8 male students and 12 female students. Student learning outcomes on the pre-cycle test the percentage of completeness reached 30% with an average value of 57, in the implementation of the first cycle the percentage of completeness reached 50% with an average value of 63,5. Cycle II reached 80% with an average value of 75,5. This shows an increase in student learning outcomes from each cycle. The increase from pre-cycle to cycle I reached 25%, and the increase from cycle I to cycle II reached 25%. The increase from pre-cycle to cycle II reached 50%. So it can be concluded that through the use of image media it can improve sicial studies learning otcomes for fourth grade students of SD Negeri 3 Molona, South Buton Regency.